Revitalizing Ecotourism in Indonesia: A Green Economy Vision Through the Lens of Fiqh Biah - Jakiyudin, Ahmad Havid; Wibisono, Vina Fithriana; Ma'shuma, Mufliha Ramadia (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2023)
Abstract: The existence of ecotourism in Indonesia needs a massive boost. Thus far, the development of ecotourism has yet to be optimal despite its significant implications in responding to the achievement of a green economy. Ecotourism offers uniqueness by prioritizing environmental conservation as a selling point and requires an appropriate development model. This research aims to address the challenges of ecotourism development based on a green economy using the alternative Fiqh Biah model. A qualitative research method with a qualitative content analysis approach was employed. The content analysis focused on ecotourism in Indonesia, the Green Economy, and Fiqh Biah. The results indicate an interconnection between ecotourism and the Green Economy regarding impacts on the economic, social, and environmental sectors. The suggested construction for ecotourism development includes: 1) Hima’: an alternative for forest-based ecotourism development, 2) Harim: a protection and mitigation system for ecotourism, and 3) Ihya al-Mawat: an opportunity to create new ecotourism by utilizing abandoned land. Abstrak: Eksistensi ekowisata di Indonesia perlu didorong lebih massif. Sejauh ini, pengembagan ekowisata belum maksimal. Meskipun implikasinya sangat besar dalam merespon pencapaian green economy. Sebab ekowisata tidak hanya mempunyai keunikan, yaitu mengutamakan konservasi lingkungan sebagai nilai jual. Konstruksi model pengembangan ekowisata yang tepat sangat diperlukan. Penelitian ini bertujuan untuk menjawab tantangan pengembangan ekowisata yang berasis green economy menggunakan alternatif model Fiqh Biah. Metode penelitian kualitatif dengan pendekatan qualitative content analysis. Analisis konten yang dimaksudkan berfokus pada topik ekowisata di Indonesia, green economy dan Fiqh Biah.  Hasil penelitian menunjukkan bahwa terdapat interkoneksi antara ecotourism dan green economy dari segi dampak pada sektor ekonomi, social dan lingkungan. Kemudian konstruksi yang disarankan untuk pengembangan ekowisata meliputi: 1) hima’: sebagai alternatif pengembangan ekowisata berbasis hutan, 2) Harim : sebagai sisten proteksi dan mitigasi ekowisata, dan 3) Ihya al-Mawat: menjadi peluang untuk menciptakan ekowisata baru dengan memanfaatkan tanah terlantar.